2021
DOI: 10.1186/s12889-021-10647-6
|View full text |Cite
|
Sign up to set email alerts
|

Scaling up public health interventions: case study of the polio immunization program in Indonesia

Abstract: Background The scaling up of public health interventions has received greater attention in recent years; however, there remains paucity of systematic investigations of the scaling up processes. We aim to investigate the overall process, actors and contexts of polio immunization scaling up in Indonesia from 1988 until 2018. Methods A mixed method study with sequential explanatory design was conducted. We carried out a quantitative survey of 323 acto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…( 30)At the community level, integrated health services posts ("Posyandu") delivered polio immunization along with maternal and child health and nutrition, which may have contributed to stronger health service delivery. (30)We found lower odds of identifying polio implementation process as a main internal contributor for strengthening service delivery in Eastern Mediterranean region. For example, in Pakistan, polio supplementary immunization activites were criticized as being disjointed from routine childhood immunization services and other primary health care services.…”
Section: Discussionmentioning
confidence: 82%
“…( 30)At the community level, integrated health services posts ("Posyandu") delivered polio immunization along with maternal and child health and nutrition, which may have contributed to stronger health service delivery. (30)We found lower odds of identifying polio implementation process as a main internal contributor for strengthening service delivery in Eastern Mediterranean region. For example, in Pakistan, polio supplementary immunization activites were criticized as being disjointed from routine childhood immunization services and other primary health care services.…”
Section: Discussionmentioning
confidence: 82%
“…Some studies showed that SMNet program continued to support routine childhood immunization, and improved primary health care service delivery in Uttar Pradesh, Bihar and West Bengal [ 14 , 17 , 29 ]. In Indonesia, the polio program was integrated in the existing sub-national government institutions for immunization [ 30 ]. At the community level, integrated health services posts (“Posyandu ” ) delivered polio immunization along with maternal and child health and nutrition, which may have contributed to stronger health service delivery [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Indonesia, the polio program was integrated in the existing sub-national government institutions for immunization [ 30 ]. At the community level, integrated health services posts (“Posyandu ” ) delivered polio immunization along with maternal and child health and nutrition, which may have contributed to stronger health service delivery [ 30 ]. We found significantly lower odds of identifying polio implementation process as a main internal contributor for strengthening service delivery in Eastern Mediterranean region.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, evidence synthesis of the barriers to and facilitators of polio eradication programs improves complex health interventions [2], especially in resource-constrained settings. Numerous researchers have documented implementation factors with regard to polio vaccination and eradication in the literature [2][3][4][5][6][7]. Systematically reviewing these lessons across nations may be relevant for the formulation and implementation of other vaccination programs.…”
Section: Introductionmentioning
confidence: 99%